LATERAL APPROACH RETROPERITONEOSCOPIC ADRENALECTOMY: A SINGLE-CENTRE MALAYSIAN EXPERIENCE - Sin, Loh Chit; Lai, Leslie; Ismail, Faridah; Kassim, Saiful; Heng, Lee Chiang; Ming, Liao Chee; Mohanavel, Thashvinatini (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION Laparoscopic or retroperitoneoscopic adrenalectomy is now the preferred approach when adrenalectomy is indicated. We report the first series of Lateral Approach Retroperitoneoscopic Adrenalectomy. METHODOLOGY Between 2013 and 2023, a total of 46 patients (28 males,18 females; mean age 48.4 years) were referred for minimally invasive adrenalectomy. The surgeon, a urologist, was trained in minimally invasive surgery and is a proponent of the lateral approach retroperitoneoscopic technique. Twenty-six cases involved the left side and 20 cases involved the right. The size of the lesions ranged from 6 to 80 mm (mean = 30). RESULT Mean surgery time was 90.8 minutes and mean hospital stay was 2.8 days. Two cases were converted to transperitoneal lateral approach due to the need to perform lymph node dissection. Two patients received blood transfusion. CONCLUSION Lateral approach retroperitoneoscopic adrenalectomy is safe and suitable for a wide range of adrenal pathologies and offers consistent clinical outcomes. When paracaval/paraaortic lymph node dissection is necessary, it can also be converted to a transperitoneal approach. Incidentalomas are common in the private sector due to ready access to axial imaging.